Industrial Services Reference Model - Gerosa, M.; Taisch, M. (Cranfield University Press, 2009)
The need to integrate service providers into an existing customer supply chain requires the collective know-how of the coordination mode, including the ability to synchronize interdependent processes, to integrate information systems and to cope with distributed learning. About this topic the EU-funded InCoCo-S project is developing a new standard business reference model with key focus on operation & integration of business related services in supply chains. Based on the requirement analysis concrete business processes have been developed to integrate services in the existing customer supply chain both on a strategic and operational level.
Organised by: Cranfield University
Keywords: Service supply chain; process modeling; reference model